2001
DOI: 10.3109/07853890109002058
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein, fibrinogen, interleukin-6 and tumour necrosis factor-α in the prognostic classification of unstable angina pectoris

Abstract: Elevated levels of acute-phase proteins and cytokines, particularly CRP and IL-6, are strong predictors of the risk of serious coronary events in patients with UAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
100
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(113 citation statements)
references
References 35 publications
8
100
0
5
Order By: Relevance
“…Their findings are consistent with ours, showing a strong predictive value for the all markers, particularly for IL-6. Similar findings were also reported by Koukkunen et al, 14 exploring the prognostic value of these 3 inflammatory markers in older patients with CHD. Perhaps, especially because of its wide range of actions, including effects on platelets, endothelium, and factors of metabolism and coagulation, IL-6 may have a more important role in the development of CHD than some other inflammatory markers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Their findings are consistent with ours, showing a strong predictive value for the all markers, particularly for IL-6. Similar findings were also reported by Koukkunen et al, 14 exploring the prognostic value of these 3 inflammatory markers in older patients with CHD. Perhaps, especially because of its wide range of actions, including effects on platelets, endothelium, and factors of metabolism and coagulation, IL-6 may have a more important role in the development of CHD than some other inflammatory markers.…”
Section: Discussionsupporting
confidence: 88%
“…5,[7][8][9][10] Moreover, few articles have explored the predictive value of inflammatory markers on cardiovascular events in cardiovascular disease-free subjects, 4,5,7,9,10,12,13 and even fewer have considered multiple markers, such as interleukin-6 (IL-6), C-reactive protein (CRP), and tumor necrosis factor-␣ (TNF-␣), simultaneously. 4,14 In fact, most studies have focused only on CRP. 9 -12,15-18 A recent longitudinal study among elderly subjects without previous myocardial infarction has shown a stronger role for IL-6 in the prediction of congestive heart failure (CHF) than for CRP or TNF-␣.…”
mentioning
confidence: 99%
“…TNFa, OX40/OX40L and RANK/ RANKL) and inhibitory (e.g. TRAIL) effects on this process [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that, also in vivo, elevated TNF-a might enhance cytokine release from monocytes to any LPS-like danger signal (e.g., related to an infection or cellular stress), thereby promoting atherosclerosis. Epidemiological data support the notion that elevated plasma levels of both TNF-a and IL-6 increase the risk of coronary artery disease (Koukkunen et al, 2001;Ridker et al, 2000a). Thus, differential regulation of monocyte-IL-6 production may provide a link from acute inflammatory cytokine release (TNF-a) to the long-term progression of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 82%
“…Elevated plasma levels of the two proinflammatory cytokines tumor necrosis factor (TNF)-a and interleukin-6 (IL-6) have been repeatedly associated with increased risk for adverse cardiovascular outcomes (Elkind et al, 2002;Koukkunen et al, 2001;Plutzky, 2001;Ridker et al, 2000a,b;Rohde et al, 1999;Ross, 1999). Inflammatory processes in atherosclerosis are overtly mediated by monocytes which are an important source of circulating cytokines (Plutzky, 2001;Ross, 1999;Vaddi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%